Accepting a crowdsourced delivery - A choice-based conjoint analysis - Henrik Bathke; Evi Hartmann (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 32, 2021)
Purpose: The increase in parcel quantities on the last mile requires new and innovative concepts to support sustainability efforts in urban areas. Crowdsourced delivery (CSD) represents a promising concept as it allows private couriers to take over the parcels' last mile on trips they would have traveled anyway. Whereas first research on the attributes leading to the acceptance of CSD requests via platforms exists, the attributes' respective importance remains unclear. Methodology: A choice-based conjoint analysis with 193 respondents willing to participate in CSDs was conducted. Attributes' relative importance and part-worth utilities were calculated using Hierarchical Bayes estimation. Findings: Results show that differences in deviation of the original travel time and remuneration have the greatest impact on couriers' request selection, while the degree of familiarity with the recipient and parcel weight are less decisive. Additionally, it became apparent that couriers' sentimental traits of environmental concerns and extraversion affect the choice of a CSD request. Originality: The study contributes to the scarce literature on the promising concept of CSD to reduce logistics-related environmental externalities and strengthens the application of marketing-related methodologies in logistics research. For CSD platform providers, results enable higher competitiveness through a more individualized request for potential couriers.
urn:nbn:de:gbv:830-882.0162220; hdl:10419/249609; https://econpapers.repec.org/RePEc:zbw:hiclpr:32
Keywords: 650; City Logistics